The principles of the formation of an integrated assessment of environmental performance of oil companies (Путеводитель предпринимателя)
The paper considers modern processes and indicators of an integrated assessment of environmental activities implemented by the major oil companies. The basic principles for the implementation of environmental activities, determined by its content.